2022
DOI: 10.1007/s00345-022-04255-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing critical temperature dose areas in the kidney by magnetic resonance imaging thermometry in an ex vivo Holmium:YAG laser lithotripsy model

Abstract: Purpose We aimed to assess critical temperature areas in the kidney parenchyma using magnetic resonance thermometry (MRT) in an ex vivo Holmium:YAG laser lithotripsy model. Methods Thermal effects of Ho:YAG laser irradiation of 14 W and 30 W were investigated in the calyx and renal pelvis of an ex vivo kidney with different laser application times (tL) followed by a delay time (tD) of tL/tD = 5/5 s, 5/10 s, 10/5 s, 10/10 s, and 20/0 s, with irrigation rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Their work sought to adapt their previous findings to an in vivo porcine model and found that temperatures capable of tissue damage were easily achieved but can be negated by increasing irrigation flow rate 15 . Other labs have also evaluated irrigation rates and have determined that increased irrigation rates can mitigate temperature increases during active lasing, as too can the use of a UAS [16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…Their work sought to adapt their previous findings to an in vivo porcine model and found that temperatures capable of tissue damage were easily achieved but can be negated by increasing irrigation flow rate 15 . Other labs have also evaluated irrigation rates and have determined that increased irrigation rates can mitigate temperature increases during active lasing, as too can the use of a UAS [16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…Concerns regarding intrarenal temperature with the use of HP have raised [35][36][37] and more studies are needed to find the limits to avoid the potential damage [38][39] especially when treating ureteral stones [40][41][42]. For this issue, temperature sensors have been proposed [43].…”
Section: Disadvantagesmentioning
confidence: 99%
“…Wriedt et al [ 20 ] evaluated tissue heating with magnetic resonance imaging in an ex vivo porcine kidney model using different lithotripsy parameters. The authors reported that an irrigation rate of at least 70 ml/min is necessary to avoid exceeding 120 min CEM 43 when using a laser application of 30 W for 10 s. Additionally, they observed a focal temperature rise on the calyx wall in experiments with human stones, which they attributed to non-elimination of heated fragmented stone pieces from the surgical area in the kidney.…”
Section: Literature Reviewmentioning
confidence: 99%